“Efectos de extractos vegetales para controlar cercospora longissima aislado de lechuga (lactuca sativa L.) en laboratorio e invernadero” - Campos Varela, Nadia Alina (2006)
The objective was to evaluate the effect of dose of vegetable extracts in the control of C. longissima in Laboratory and hothouse of the UNSM - T. For the test in Laboratory it gathered samples of leaves of Lactuca saliva L affected with the illness. The extracts got ready weighing 100 g of each plant. The leaves were crushed in a mortar and a pylon, the seeds were milled adding distilled water and macerating for 24 h. For this test the Design was used Totally at random (DCA} with factorial arrangement 10 (you plant} x 4 (dose: O mi, 1 mi, 2 mi and 4 mi) and the duncan test (at the 0,05). In this test the extracts of Ch. ambrosoides (1ml), A indica (1 mi, 2 mi and 4 mi), R. communis (1 mi) and S. torvum (4 mi and 2 mi), they obtained positiva effect on C. longissina with averages of size of colony of 1,582; 1,579; 1 ,54; 1,384; 1 ,537; 1 ,384 and 1 ,38 cm respectively, being statistically inferior to the witness (2,3 cm). In the hothouse phase, a design was used totally at random (DCA) of 7 treatments with 5 observations and the test of Duncan at the 0,05: obtaining results for the percentage of incidence with the extracts of S. torvum (20 mili) Rosa sp (20 mili) and Ch. ambrosioides (10 mili) with 23, 18%; 33% and 26, 1% respectively, also for the number of stains for leaf with 3,26; 3,54 and 6,2 stains. For the percentage of severity the extracts of S. torvum and A indica they had percentage of AFA of 2,46% and 1,24% reaching grade respectively 1 and for the percentage of efficiency of extracts they were A. it indicates, S. toNum and Rosa sp., those that had 91,66%; 91,22% and 89,64% respectively in the control of C. longíssíma.